2018
DOI: 10.1016/j.jval.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ultrasound Thalamotomy and Other Interventions for Medication-Refractory Essential Tremor: An Indirect Comparison of Short-Term Impact on Health-Related Quality of Life

Abstract: Background: Up to 50% of essential tremor patients are refractory to medication and require alternative treatment to achieve tremor relief. This study aimed to identify and analyze evidence supporting the use of the emerging magnetic resonance-guided focused ultrasound (MRgFUS) compared to alternative stimulatory and ablative interventions for the treatment of medication-refractory essential tremor: radiofrequency thalamotomy, unilateral deep brain stimulation (DBS), and stereotactic radiosurgery. Methods: A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…MRgFUS may provide certain advantages over other surgical interventions due to it being a non-invasive procedure 101 108 118. A recent systematic literature review concluded that the efficacy in tremor control as well as improving quality of life with unilateral MRgFUS-thalamotomy might be comparable to unilateral DBS in the short term up to 12 months after procedure 119. On the other hand, DBS is the favoured treatment in subjects with bilateral and axial tremor as well as in those with contraindications to undergo MRI before the procedure 72 73 76–78 83 101 115…”
Section: Surgical Interventions For Etmentioning
confidence: 99%
“…MRgFUS may provide certain advantages over other surgical interventions due to it being a non-invasive procedure 101 108 118. A recent systematic literature review concluded that the efficacy in tremor control as well as improving quality of life with unilateral MRgFUS-thalamotomy might be comparable to unilateral DBS in the short term up to 12 months after procedure 119. On the other hand, DBS is the favoured treatment in subjects with bilateral and axial tremor as well as in those with contraindications to undergo MRI before the procedure 72 73 76–78 83 101 115…”
Section: Surgical Interventions For Etmentioning
confidence: 99%
“…On the other hand, a recently published retrospective chart review compared 59 patients who had undergone unilateral MRgFUS, DBS, or RF at a medical center in Korea and found no difference in proportions of treatment success between surgeries . In addition, a recently published systematic literature review and indirect treatment comparison study also found no difference in efficacy (measured by Clinical Rating Scale for Tremor Total) and HRQoL (measured by Clinical Rating Scale for Tremor Part C) outcomes between MRgFUS and unilateral DBS in the short‐term (≀12 months) . We assessed the cost‐effectiveness of MRgFUS compared with standard treatments in 2 distinct patient populations: those who were ineligible for invasive neurosurgery and those who were eligible.…”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, a recently published systematic literature review and indirect treatment comparison study also found no difference in efficacy (measured by Clinical Rating Scale for Tremor Total) and HRQoL (measured by Clinical Rating Scale for Tremor Part C) outcomes between MRgFUS and unilateral DBS in the short-term (≀12 months). 38 We assessed the costeffectiveness of MRgFUS compared with standard treatments in 2 distinct patient populations: those who were ineligible for invasive neurosurgery and those who were eligible. Our analysis comparing MRgFUS with no surgery in people ineligible for invasive neurosurgery was based on a randomized, double-blind, placebocontrolled trial, 12 a study design considered to provide robust evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Based on an assumption of equal efficacy, a cost-minimisation model from a Japanese healthcare payers’ perspective was used to compare MRgFUS to unilateral DBS, capturing only direct healthcare costs [15, 30–32]. All model costs were estimated using 2018 Japanese Yen (JPY) except where explicitly stated in analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from a small retrospective analysis and an indirect treatment comparison (ITC) of MRgFUS and unilateral DBS with 12 months follow-up shows that these procedures provide similar relief from tremor and its associated disabilities [15, 30]. Therefore, a cost-minimisation model, which assumes equal efficacy for each included procedure, can be considered an appropriate approach for comparing the costs of MRgFUS to unilateral DBS across a 12-month time horizon.…”
Section: Introductionmentioning
confidence: 99%